Analysis of physical collisions in elite national rugby league match play - Cummins, C.; Orr, R. (International Journal of Sports Physiology and Performance, 2015)
Objective: To investigate the impact forces of collision events during both attack and defense in elite rugby league match play and to compare the collision profiles between playing positions. Participants: 26 elite rugby league players. Methods: Player collisions were recorded using an integrated accelerometer in global positioning system units (SPI-Pro X, GPSports). Impact forces of collisions in attack (hit-ups) and defense (tackles) were analyzed from 359 files from outside backs (n = 78), adjustables (n = 97), wide-running forwards (n = 136), and hit-up forwards (n = 48) over 1 National Rugby League season. Results: Hit-up forwards were involved in 0.8 collisions/min, significantly more than all other positional groups (wide-running forwards P = .050, adjustables P = .042, and outside backs P = .000). Outside backs experienced 25% fewer collisions per minute than hit-up forwards. Hit-up forwards experienced a collision within the 2 highest classifications of force (=10 g) every 2.5 min of match play compared with 1 every 5 and 9 min for adjustables and outside backs, respectively. Hit-up forwards performed 0.5 tackles per minute of match play, 5 times that of outside backs (ES = 1.90; 95% CI [0.26,3.16]), and 0.2 hit-ups per minute of match play, twice as many as adjustables. Conclusions: During a rugby league match, players are exposed to a significant number of collision events. Positional differences exist, with hit-up and wide-running forwards experiencing greater collision events than adjustables and outside backs. Although these results may be unique to the individual team`s defensive- and attacking-play strategies, they are indicative of the significant collision profiles in professional rugby league.